Kimco Metal Sdn. Bhd. a Case Study - Khoo, Kok Leong (1997)
The business environment in 1990s has been changed dramatically compared to the past two to three decades. New management and marketing concepts have evolved in such rapidity and being fine tuned in suiting to each corresponding industry. Information technology have been much flourished and being widely applied in communication and the related industry. This has shortened the barrier of distance and hence resulted the competition became more tense in the 1990s business environment. The industry of building material, being a supplier or trader will undoubtedly face tough challenges despite the booming economic growth in recent years. Entry barrier to the industry is low and the start-up cost might not intensive. This resulted a high numbers of new rivals in the market every years. Profit is marginal as it is diluted by these runner-up firms. The competition in the industry is intensive due to the end-run and guerrilla offensives by the these firms. The whole market has thus become cost conscious. Presented here, is a case study that looked into the problem of both sales and profit decline due to the described industry scenario. There is a search of the modem marketing management concepts to be adopted in a medium size distributor's daily business operations. However, any transformational changes could not be actualized overnight. It requires identification of problems, persistent planning and implementation of such concepts to achieve a paradigm shift.